Study on the Effect of Sodium Silicate Solution Injection Timings on Electrochemical Reinforcement of Dredged Sludge - Jiangdong Lin; Mi Ai; Guohui Yuan; Long Wang; Ziyang Gao; Xiaobing Li; Hongtao Fu; Yongfei Fan (Buildings)
To address the issue of uneven shear strength distribution in dredged sediment during electroosmosis treatment, a grouting system was employed to inject CaCl2 into the anode region and Na2SiO3 solution into the central region. An experimental study was conducted to examine the effect of injection timing on the electrochemical treatment of dredged sediment. Five experimental groups, each with different Na2SiO3 injection timings, were established. The impact of injection timing on the macroscopic electrochemical reinforcement was assessed based on current, drainage volume, settlement, moisture content, and shear strength. Additionally, the ion concentration of effluent from the cathode was measured, and scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) were employed to analyze ion migration and pore characteristics. The results indicated that when CaCl2 was injected into the anode at the start of the experiment and Na2SiO3 was injected into the central region after the current had decayed by 70% from its peak, the drainage volume reached its maximum. Under these conditions, the average shear strength increased from nearly 0 kPa to 48.2 kPa, yielding the optimal reinforcement effect. The strength in both the central and cathode regions also improved, and the strength distribution between the anode and cathode became more uniform, with the strength ratio decreasing from 1.91 to 1.65, thereby enhancing the overall soil strength distribution. The Na+ concentration in the cathode effluent was highest, suggesting that Na+ migration played a predominant role in electroosmotic drainage. Furthermore, the electrochemical reactions generated cementitious materials that effectively filled the soil pores. SEM imaging and MIP pore size analysis revealed a reduction in porosity and an increase in soil compaction.